The 19th century Old Believers’ chased icon “Cross of Calvary” as a heritage of Old Russian Staurotheke - Valeriy V. Igoshev (Russian Journal of Church History, 2022)
This article examines the chased relief icon “Cross of Calvary” made on a thin brass plate fastened to a rectangular wooden board. The chased icon compositional construction and the inscriptions-cryptograms are similar to the wood-carved Old Believers’ icons of the 18th — 19th centuries made by masters of the Russian North. The general composition, the style of the ornament, the technique of execution and the inset inscription on the engraved icon “Cross of Calvary” testify that this work was created by an Old Believers master, a follower of the Old Pomor community Filippovtsy in the Russian North in the first half of the 19th century and is focused on the oldest traditions of church art. The chased relief icon depicting the eight-pointed Calvary Cross is an echo of the ancient tradition of creating a Staurotheke, well-known in ancient Russian and Byzantine art. Such icons did not only belong to churches but also were carefully kept as family relics in the Cross chambers or in the Red corners of the living quarters and subsequently contributed to the church. Making of a Staurotheke is associated with the veneration and preservation of liturgical or pectoral crosses, which were cut into a board or placed in closed arks then becoming an icon of the Cross. Those Staurothekes were сonsidered to be sacred objects richly decorated with oklads, precious stones and pearls. This article also presents various types of liturgical and pectoral crosses with embedded sacred relics, which were especially revered. Old Russian crosses were made in different periods of time with different art styles, shape, proportions, sizes, nature of decor. All this indicates a variety of traditions and revered sanctities which served as models in the process of making later crosses.